SMEs for Job Creation in the Arab World : SME Access to Financial Services - Nasr, Sahar; Pearce, Douglas (World Bank, Washington, DC, 2017)
The Arab Spring in the Middle East and North Africa (MENA) region has brought to the forefront key challenges: the need to create job opportunities, equal access, a level playing field, transparency and accountability, and a fair and competitive environment. Crony capitalism, the privileged access of certain elites to favorable legal and regulatory treatment, access to markets, and the coincidence of political and economic power, was a major concern contributing to the uprising. Many saw privilege and corruption as the source of unemployment and inequality, effectively raising barriers to entry and growth for the majority of entrepreneurs. At the same time, practices such as connected lending and preferential land allocations, contributed to poor performance of key institutions, underpinning the market economy. It is critical for the MENA countries to achieve the aspirations of their people and attain sustainable and inclusive development by expanding private-led employment and creating entrepreneurship opportunities. This report assesses the supply and demand of financial services to small and medium enterprises (SMEs) in the MENA region, as well as the regulatory, institutional and policy environment that determines the cost, risk, and scale of SME finance. Emerging and promising SME finance models for banks, investors, government and regulators are outlined. These could significantly improve the outreach, viability, risk management, and development impacts of SME finance in the MENA region. SMEs need access to longer term credit products and equity, in addition to working capital loans and trade finance. They also need payment and card services, deposit facilities, liquidity management, risk management tools and insurance. The principal role of the state is as an enabler and regulator, providing the financial infrastructure, and legal and policy frameworks that financial institutions need to be able to meet the range of SME financial needs profitably. All this will contribute to attaining a more sustainable and inclusive system that can play a more important role in economic growth, and the regions prosperity.